Preparation of Near-Infrared/Photoacoustic Dual-Mode Imaging and Photothermal/Chemo Synergistic Theranostic Nanoparticles and Their Imaging and Treating of Hepatic Carcinoma - Zhou, Yun; Lin, Bixia; Li, Kai; Zhao, Yufeng; Sun, Zhuo; He, Chenchen; Jha, Rajiv Kumar (Frontiers in Oncology, 2021)
At present, the clinical diagnosis and treatment methods of hepatic carcinoma are still hardly meet the needs. The integrated theranostic system, in which functional materials are used to load different active molecules, created a new development direction for the combination treatment of hepatic carcinoma, realizing the synchronization of diagnosis and treatment. In this study, polydopamine (PDA), which has the functions of self-assemble, encapsulation, photothermal conversion, and photoacoustic interaction, was used as the carrier material. The IR780, a near-infrared fluorescence imaging (NIFI), photoacoustic imaging (PAI), and photothermal therapy (PTT) agent, and paclitaxel (PTX), a broad-spectrum chemotherapy drug, were selected to build the NIF/PA dual-mode imaging & PTT / chemo synergistic theranostic nanoparticles (DIST NPs). The DIST NPs have a 103.4 ± 13.3 nm particle size, a weak negative charge on the surface, good colloidal stability, slow and controlled drug release, and high photothermal conversion ability. The experiments results showed that the DIST NPs have long circulation in vivo, high bioavailability, high biocompatibility, and low effective dose. DIST NPs showed excellent NIFI/PAI dual-mode imaging and significant synergistic antitumor effect in hepatic carcinoma models. DIST NPs met the initial design requirements. A set of fast and low-cost preparation methods was established. This study provides an experimental basis for the development of new clinical theranostic methods for hepatic carcinoma.